Leadership Style as a Mediator Between Employee Competence and Performance in Islamic Banking: A Case Study of BSI Area Banjarmasin - Wulansari, Intan Wulansari; Said, Laila Refiana (Ilomata International Journal of Management, 2026)
This study examines the effect of employee competence on performance and tests whether leadership style mediates this relationship in Bank Syariah Indonesia (BSI) Area Banjarmasin. Competence is positioned as a core dimension of human resource development that enhances work effectiveness, while leadership style shapes the extent to which competence is translated into employee performance. A quantitative survey was conducted with 60 employees purposively selected from six BSI sub-branch offices. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS. The results show that (1) competence has a positive effect on leadership style; (2) leadership style positively affects employee performance; (3) competence directly improves employee performance; and (4) leadership style significantly mediates the competence–performance relationship. The structural model explains 76.9% (R² = 0.769) of the variance in employee performance, demonstrating a robust model with strong predictive power for employee outcomes in Islamic banking. This study contributes to Islamic banking and organizational behavior literature by clarifying how contextually grounded leadership style mediates the competence–performance link in a Sharia-compliant banking environment.